Organic Farming : Global Perspectives and Methods - Chandran, Sarath, 1978-; Unni, M. R.; Thomas, Sabu (Duxford, United Kingdom : Woodhead Publishing is an imprint of Elsevier, 2019)
Organic Farming: Global Perspectives and Methods explores the core definition and concepts of organic farming in sustainability, its influence on the ecosystem, the significance of seed, soil management, water management, weed management, the significance of microorganisms in organic farming, livestock management, and waste management. The book provides readers with a basic idea of organic farming that presents advancements in the field and insights on the future. Written by a team of global experts, and with the aim of providing a current understanding of organic farming, this resource is valuable for researchers, graduate students, and post-doctoral fellows from academia and research institutions.
Includes bibliographical references and index.
Keywords: Organic farming